SOME PROBLEMS OF PROTECTION OF COMMERCIAL SECRETS - Diduk, Alla; Lytvyn, Stepan (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of this article is to clarify some of the problems of trade secret protection and suggest ways to overcome them. The methodological basis of the study are general and special methods of cognition. The use of these methods made it possible to describe the problems of trade secret protection. Results: the study found that breaches of trade secrets are considered by international law as unfair competition. At the same time, the laws on unfair competition in the countries of the continental (pandectic) legal system are based on the theory of confidentiality (de facto monopoly). Therefore, the foreign experience of the countries of the continental (pandect) system of law is of particular importance for the formation of Ukrainian legislation on trade secrets. Discussion: given the specifics of the studied object of intellectual property rights and based on the analysis of international experience found that national approaches to ways to protect intellectual property rights to trade secrets are not effective because they do not provide and do not provide maximum material satisfaction for the person access to which is violated, and quite severe consequences for the offender. It is proposed to improve the current legislation of Ukraine on the protection of trade secrets.